АРХІТЕКТУРА ГРОМАДСЬКИХ БУДИНКІВ ТА КОМПЛЕКСІВ У УМОВАХ ДЕМОГРАФІЧНОГО ПЕРЕХОДУ - Шулдан Л. О. (World Science, 2019)
Trends in the development of public buildings’ architecture and complexes in the near future are determined, among other, by a demographic factor. It is suggested to conduct the analysis of the demographic situation on three levels: the macro level (global processes); the meso level (state) the micro level (region, city, village, etc.). The following indicators are determined at each level: the existing population; sections of age and gender groups; the proportion of rural and urban population. Which have been studied in the dynamics. Public buildings are most sensitive to demographic shifts. Thus, changes in public buildings’ structure would consist in: the growing role in the context of rapid urbanization; redistribution, development and appearance of their new types in accordance with the needs of a progressive cell (gerontological, educational, palliative, etc.) the predominance of modernization, expansion and renovation to new construction; providing polyfunctionality; maximum use of innovative arrangements and techniques. Presented analysis formed the basis for improving the energy efficiency of public buildings and complexes.